The Performance of Treatment Train System Incorporated with Nature-Based Materials in Capturing Nutrient for Stormwater Runoff - Ali, W. (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
Biofilters, commonly called rain gardens, are becoming increasingly popular among best-management practices (BMPs). They have recently sparked significant interest due to their ability to control stormwater quality. These systems face challenges in manipulating dissolved nitrogen and phosphorus species. This study reports the results of the removal of nitrogen and phosphorus in two modified bioretention systems. The performance of modified bioretention with coconut and durian was compared. The modified bioretention system was evaluated as a single and a series. Sequencing these systems in a series maintained the continuity of nutrient removal. Both series efficiently removed NH3-N (97 in TC5, 95 in TD5), while the removal of NO3-N was moderate (65 inTC5, 67 in TD5). Good removal efficiencies of TP were observed in two series (84 in TC5, 81 in TD5). However, the PO4 removal was equalized in all series (98). The TN and ON removal were poor and fluctuated with time and column number in TC5, the overall removal efficiencies were (69 and 43), respectively, while in TD5 a significant fraction of TN and ON were removed (86 and 78), respectively. As compared with coconut husk, durian peel is considered a promising material that can enhance the water quality in bioretention systems. Â© 2022. Journal of Ecological Engineering. All Rights Reserved.